2006
DOI: 10.1105/tpc.105.038745
|View full text |Cite
|
Sign up to set email alerts
|

BlindHomologousR2R3 MybGenes Control the Pattern of Lateral Meristem Initiation inArabidopsis

Abstract: In seed plants, shoot branching is initiated during postembryonic development by the formation of secondary meristems. These new meristems, which are established between the stem and leaf primordia, develop into vegetative branches or flowers. Thus, the number of axillary meristems has a major impact on plant architecture and reproductive success. This study describes the genetic control of axillary meristem formation in Arabidopsis thaliana by a group of three R2R3 Myb genes, which are homologous to the tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
263
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(267 citation statements)
references
References 37 publications
4
263
0
Order By: Relevance
“…LS, LAS, and MOC1 are orthologous genes encoding transcriptional regulators of the GRAS family (Schumacher et al, 1999;Greb et al, 2003;Li et al, 2003). BL and RAX are also orthologous genes that encode R2R3-type Myb transcription factors (Schmitz et al, 2002;Keller et al, 2006;Mü ller et al, 2006). This shows that AM formation may be regulated by a conserved mechanism in different plant species, including monocots and eudicots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LS, LAS, and MOC1 are orthologous genes encoding transcriptional regulators of the GRAS family (Schumacher et al, 1999;Greb et al, 2003;Li et al, 2003). BL and RAX are also orthologous genes that encode R2R3-type Myb transcription factors (Schmitz et al, 2002;Keller et al, 2006;Mü ller et al, 2006). This shows that AM formation may be regulated by a conserved mechanism in different plant species, including monocots and eudicots.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the defective genes in these mutants are probably involved in mechanisms that control general aspects of meristem initiation or function unless AM formation is affected as a secondary consequence of these mutations. The other class of mutants, comprising Arabidopsis thaliana lateral suppressor (las) and regulator of axillary meristem (rax) mutants, tomato (Solanum lycopersicum) lateral suppressor (ls) and blind (bl), maize (Zea mays) barren stalk1 (ba1), and rice (Oryza sativa) monoculm1 (moc1) and lax panicle1 (lax1) show AM-specific defects (Schumacher et al, 1999;Komatsu et al, 2001Komatsu et al, , 2003Ritter et al, 2002;Schmitz et al, 2002;Greb et al, 2003;Li et al, 2003;Keller et al, 2006;Mü ller et al, 2006). These AM-specific mutants can be further divided into two classes: either the mutant shows developmental specific defects or all AMs are affected regardless of the plant's developmental stage.…”
Section: Introductionmentioning
confidence: 99%
“…The NAC domain transcription factors CUC1,2,3 play a role in axillary meristem initiation in Arabidopsis, but in rice, overexpression of OsTIL1 enhances axillary meristem outgrowth rather than initiation (Vroemen et al, 2003;Hibara et al, 2006;Mao et al, 2007;Raman et al, 2008). R2 R3 Myb transcription factors RAX1,2,3/BLIND (Schmitz et al, 2002;Keller et al, 2006;Muller et al, 2006) play a role in eudicots, but a homolog in monocots has not yet been identified. Therefore, the roles of these transcription factors still need to be clarified in monocots.…”
Section: Role Of Auxin In Axillary Meristem Initiation During Vegetatmentioning
confidence: 99%
“…However, the molecular mechanisms that control branching in eudicots are not completely conserved with tiller development in grasses (Kebrom et al, 2013;Hussien et al, 2014;Waldie et al, 2014). For example, the reduced-branching mutations in the REGULATOR OF AXILLARY MERISTEMS1, REGULATOR OF AX-ILLARY MERISTEMS2, REGULATOR OF AXILLARY MERISTEMS3, and BLIND genes of Arabidopsis and tomato (Schmitz et al, 2002;Keller et al, 2006;Müller et al, 2006) are conserved in eudicots but have not been identified in monocot genomes (Keller et al, 2006;Müller et al, 2006).…”
mentioning
confidence: 99%